2017
DOI: 10.1097/bpb.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive intralesional excision of extremity-located osteoid osteomas in children

Abstract: In this retrospective study, we evaluated the efficiency of minimal invasive intralesional extended curettage in the treatment of osteoid osteomas of the extremities in children. Forty-seven children (29 males, 18 females; mean age 10.5 years; range 4-19 years) with osteoid osteoma of the extremities underwent minimal invasive intralesional extended curettage. The exact localization of the nidus was determined preoperatively by thin-section (1-1.5 mm) computed tomography scans, and complete excision of the nid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…23 Erol et al reported immediate and complete pain relief after minimally invasive intralesional extended curettage for OOs in 47 children. 24 Rosenthal et al demonstrated complete pain relief with following CT-guided RFA in 112 of 126 (89%) procedures. 25 However, Papathanassiou et al reported pain recurrence in three OOs (10%), one intra-articular medullary, and two extra-articular cortical lesions at 2, 6 and 4 months after RFA, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Erol et al reported immediate and complete pain relief after minimally invasive intralesional extended curettage for OOs in 47 children. 24 Rosenthal et al demonstrated complete pain relief with following CT-guided RFA in 112 of 126 (89%) procedures. 25 However, Papathanassiou et al reported pain recurrence in three OOs (10%), one intra-articular medullary, and two extra-articular cortical lesions at 2, 6 and 4 months after RFA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They had no surgical complications, including injury to neurovascular structures, infection, and wound problems with no local recurrence after 12-month follow-up. 24 However, the femoral neck and pelvis were not included in this series.…”
Section: Discussionmentioning
confidence: 99%
“…In the series of Rosenthal et al [6] in 125 patients, they report one girl 3 yrs old with OO of the femur. Recently, Erol et al [7] report that 47 children with OO had a range of ages 4-19 years old. Song et al [8] report on 43 children with range 4.2 to 15.9 for the boys and 6.2 to 13.5 years for the girls.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the lesions of the femur, we completed our procedures with RF ablation, after the removal of the bone. Minimal invasive excision of OO was reported with 3-6 cm incision for the femur and gradual removal of sclerotic bone until visualization of the small nidus that appears as a red spot [7]. We preferred CT-guided biopsy as it has even less bone exposure and is safe for the subcutaneous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A currently used minimally invasive treatment method of osteoid osteoma, which is a benign but very painful small bone tumor, involves thermal ablation under radiographic or computed tomography-controlled application [ 6 ]. With this treatment, bone tissue is destroyed through the application of targeted heat using electrocautery.…”
Section: Introductionmentioning
confidence: 99%